Human Factors Engineering in System Design: A Roadmap for Improvement - LEVA, CHIARA (My University, 2015)
This paper summarises current industrial practices and standards promoting Human Factors Engineering (HFE) at design stage and revise them with an action research approached based on the concrete case studies performed during a European project called TOSCA. The paper highlights how HFE can significantly impact the costs and risk associated with a plant lifecycle and the current gaps and issues encountered. The gaps identified are used to guide industrial practices and standards towards a more valuable inclusion of Human Factors knowledge in structured system design processes to support human performance and reduce the potential for human errors in operations and maintenance.
Keywords: Human Factors Engineering; Maintainability; Human Machine interface; System Safety Engineering